2001
DOI: 10.1046/j.1365-201x.2001.171001087.x
|View full text |Cite
|
Sign up to set email alerts
|

A subset of cingulate cortical neurones is specifically activated during alcohol-acquisition behaviour

Abstract: Activity of the 118 neurones was recorded from the cingulate cortex. The comparison of activity of each neurone in AAB and food-acquisition behaviour (FAB) enabled us to reveal that their subservings overleap substantially but not completely: 41% of 'common neurones' involved in the subserving of both FAB and AAB as well as 5% of 'alcohol-neurones' (alcohol-acquisition specific cells) were found. We think of the latter neurones as units that were specialized during the forming of alcohol-seeking behaviour. Thu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
19
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 38 publications
4
19
0
Order By: Relevance
“…Patterns of task-related neuronal activations in the cortex were shown to depend on the previous training history [12] [57]. All the mentioned data and our results are in a line with suggestion that during the first stage of learning-"mismatch" stage-previously learned behaviors and previously acquired neuronal ensembles are temporary reorganized; this process was called "accommodative reconsolidation" [58].…”
Section: Discussionsupporting
confidence: 90%
“…Patterns of task-related neuronal activations in the cortex were shown to depend on the previous training history [12] [57]. All the mentioned data and our results are in a line with suggestion that during the first stage of learning-"mismatch" stage-previously learned behaviors and previously acquired neuronal ensembles are temporary reorganized; this process was called "accommodative reconsolidation" [58].…”
Section: Discussionsupporting
confidence: 90%
“…This would suggest additional modifi cation of neurons already specialized in relation to the fi rst skill, i.e., undergoing the processes of accomodatory reconsolidation on formation of the second skill [Alexandrov et al, 2001]. The involvement of a neuron in the new learning may depend on the previous history of its electrical activity [Guzowski, et al, 2006] and may be linked with increased membrane excitability [Silva, et al, 2009].…”
Section: Discussionmentioning
confidence: 99%
“…Several neuronal recording studies have shown associations between sensory stimuli and the expectation of various outcomes, such as reward, or pain (19)(20)(21)(22)(23)(24). Finally, in several imaging studies of patients with disturbances in motivation and reward expectation, such as obsessive-compulsive disorder and drug abuse, the anterior cingulate has shown increased activation when compared with anterior cingulate in normal subjects (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38).…”
mentioning
confidence: 99%